Generalization of Tail Inequalities for Random Variables in the Martingale Theory (Contemporary Mathematics, 2022)
We generalize the tail Doob's inequality, concerning two non-negative random variables, arising in the martingale theory, in three directions: on the more general source data, on the random variables belonging to the so-called Grand Lebesgue Spaces, as well as on the multidimensional variables. We also provide several examples. Moreover we show the exactness of the estimates obtained in the particular case of positive random variables having exponential distribution.
Keywords: martingale, random variable, expectation, tail of distribution, probability space, Doob's inequality, Grand Lebesgue spaces, Young-Fenchel transform